Colocalization of (TTAGGG)n telomeric sequences and ribosomal genes in Atlantic eels - SALVADORI, SUSANNA; DEIANA, ANNA MARIA; COLUCCIA, ELISABETTA; FLORIDIA G; ROSSI E; ZUFFARDI O. (1995)
The distribution of (TTAGGG)n telomeric repeats was studied in chromosomes of two Atlantic eels,Anguilla anguilla andA. rostrata. We found that these sequences hybridize to all the telomeres but also to the entire nucleolar organizer region (NOR) localized in both species at the short arm of chromosome 8. This was considered to be due to the interspersion of telomeric sequences within the NOR ones. Whatever the significance of this interspersion may be, it seems to be limited toA. anguilla andA. rostrata since inMuraena helena (family muraenidae), which also belongs to the Anguilliformes, no telomeric hybridization signals were found along the NOR regions.